Mantle Cell Lymphoma Masquerading as obstructive sleep apnoea - Ishak, Noor Liza; Teng, Tan Sui; Mahat, Mahfida (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Tonsillar malignancy typically presents with asymmetrical tonsillar enlargement, lesion on the tonsils, sore throat or a neck mass. We report a case of unsuspected tonsillar malignancy in a 56-year-old gentleman who presented with symptoms of obstructive sleep apnoea. His tonsils were grade III bilaterally with normal mucosa. Tonsillectomy was performed to improve patient’s compliance with Continuous Positive Airway Pressure (CPAP) therapy. These tonsillar specimens were reported to be Mantle Cell Lymphoma (MCL) based on the histology and ancillary studies. This case highlights that benign-looking symmetrical tonsillar enlargement can harbour occult malignancy. It is important to note that OSA symptoms may be the presentation for haematological malignancies. Tonsillar specimens should be sent for histopathological examination regardless of the indication to avoid misdiagnosis and delay in treatment.